Research in Boraginaceae: A new variety of Cryptantha maritima, Cryptantha pondii resurrected, and Johnstonella echinosepala transferred back to Cryptantha - Simpson, Michael G.; Rebman, Jon P. (Phytotaxa, 2021)
A review of the species Cryptantha maritima (Boraginaceae) supports the continued recognition of the three varieties, these differing in corolla size, ovule and nutlet number, and calyx vestiture. Mapping of these taxa from verified specimens demonstrates some geographic trends, but also some overlap in ranges. In the process of our study, we discovered a new taxonomic entity. Cryptantha maritima var. vizcainensis is described as new. This variety is restricted to the Vizcaíno Desert of Baja California Sur, Mexico and should be considered rare, as it is known to date from only eleven collections. It differs from the other three varieties of the species in having a canescent, appressed-strigose stem vestiture lacking spreading trichomes, in having a relatively large corolla, and in having a fruit derived from two 1-ovuled ovary lobes, developing into two heteromorphic nutlets. We also discovered that the species Cryptantha pondii, previously treated as a synonym of C. patula, should be resurrected as a distinct taxon. Cryptantha pondii is restricted to the western Vizcaíno Desert and to Natividad Island of Baja California Sur. It is morphologically distinctive in having bracteate flowers, relatively large corollas, and four smooth nutlets heteromorphic by size. It is to date known from only three collections and should be considered extremely rare. We also reviewed the morphological and phylogenetic status of Johnstonella echinosepala. This taxon shows similarities to Cryptantha maritima and also exhibits some morphological discontinuity between Pacific and Gulf populations in Baja California Sur. Evidence from both morphological and phylogenetic studies supports the transfer of this species from the genus Johnstonella back to the genus Cryptantha. Finally, we propose that both C. pondii and C. echinosepala are likely close relatives of C. maritima, all of the “Maritimae clade,” a group distantly related to the main core of the genus Cryptantha. This study confirms the great importance of studying herbarium specimens in taxonomic research.